"Diamond stage" in Sino-Croatian relations - Bakota, Ivica (Array, 2020)
By borrowing an ad hoc concept 'diamond stage' uttered by Chinese Premier Li Keqiang during his visit to Croatia in April 2019 to describe a new stage in Sino-Croatian bilateral relations, this article sets to analyse the reasons behind this flattering diplomatic designation. It departs from the context of weak, historically distant and asymmetrical Sino-Croatian cooperation (SCC), giving, firstly, a short account on historical relations between China and Croatia and, secondly, relying on small state power scholarship in IR, depicting the opening and advancing of SCC. While categories of state size, geographical proximity, bilateral history and relational capacity are relatively pointless given the previous track of SCC, the dynamics of decreasing asymmetry between a small state and a big power helps to understand the recent upcoming of a new, 'diamond' stage in bilateral relations. Therefore, the article proposes several features as particularly relevant for understanding decreased asymmetry in SCC.